Shouting Catfish and Subjugated Thunder God: A Popular Deity’s Criticism of the Governmental Authority in the Wake of the Ansei Edo Earthquake in Catfish Prints - Kumiko McDowell (Arts)
Soon after the devastating Ansei Edo earthquake in 1855, popular prints known as catfish prints (namazu-e) circulated widely. These prints were rooted in the folk belief that a giant catfish beneath the earth caused earthquakes. Various types of catfish prints were published: some depicted a punished earthquake catfish and served as protective charms against future quakes, while others functioned as sharp social commentary. In the latter type, the catfish was portrayed as a popular deity capable of bringing favorable societal change for people in the lower social class, symbolizing hope for commoners through reduced economic disparities after the disaster. The print “Prodigal Buddha” positioned the catfish as an antihero, criticizing the Tokugawa government’s inefficacy and the failure of religious institutions to provide spiritual salvation. By juxtaposing the catfish—now a newly popular deity—with a thunder god, formerly a fearsome deity but now submissively obeying the catfish, the print effectively visualizes the shift in status between the two. This article examines the criticism directed at political and religious authorities in the aftermath of the disaster, analyzing the layered symbolism of the thunder gods in the print.